2011
DOI: 10.3402/pba.v1i0.7219
|View full text |Cite
|
Sign up to set email alerts
|

Broad segmental progeroid changes in short-lived Ercc1 −/Δ7 mice

Abstract: Genome maintenance is considered a prime longevity assurance mechanism as apparent from many progeroid human syndromes that are caused by genome maintenance defects. The ERCC1 protein is involved in three genome maintenance systems: nucleotide excision repair, interstrand cross-link repair, and homologous recombination. Here we describe in-life and post-mortem observations for a hypomorphic Ercc1 variant, Ercc1−/Δ7, which is hemizygous for a single truncated Ercc1 allele, encoding a protein lacking the last se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
156
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(167 citation statements)
references
References 26 publications
10
156
1
Order By: Relevance
“…To verify the presence of an 8-oxoG and abasic site (THF residue) in the loop region of the substrates, we initially probed the formation of hairpins in the CAG repeat tract of the substrates using ssDNA-specific nucleases, Mung Bean Nuclease and S1 Nuclease. We found that Mung Bean Nuclease cleavage on the (CAG) 7 14 -THF hairpin substrate, the nuclease cleavage led to production of products with 45, 48 and 52 nt (Figure 2.3, lanes 7-9), whereas S1 Nuclease cleavage on the (CAG) 14 -8-oxoG and (CAG) 14 -THF hairpin substrates resulted in products with 45, 49, 51 and 54 nt (Figure 2.2 and 2.4, lanes 7-9). This indicates that the substrates contained a hairpin with a (CAG) 4 loop with an 8-oxoG or THF residue and 10 CAG repeats in the stem region.…”
Section: A Dna Base Lesion Located In a Cag Repeat Hairpin Loop Can Bmentioning
confidence: 88%
See 4 more Smart Citations
“…To verify the presence of an 8-oxoG and abasic site (THF residue) in the loop region of the substrates, we initially probed the formation of hairpins in the CAG repeat tract of the substrates using ssDNA-specific nucleases, Mung Bean Nuclease and S1 Nuclease. We found that Mung Bean Nuclease cleavage on the (CAG) 7 14 -THF hairpin substrate, the nuclease cleavage led to production of products with 45, 48 and 52 nt (Figure 2.3, lanes 7-9), whereas S1 Nuclease cleavage on the (CAG) 14 -8-oxoG and (CAG) 14 -THF hairpin substrates resulted in products with 45, 49, 51 and 54 nt (Figure 2.2 and 2.4, lanes 7-9). This indicates that the substrates contained a hairpin with a (CAG) 4 loop with an 8-oxoG or THF residue and 10 CAG repeats in the stem region.…”
Section: A Dna Base Lesion Located In a Cag Repeat Hairpin Loop Can Bmentioning
confidence: 88%
“…Substrates containing a (CAG) 7 or (CAG) 14 hairpin with an 8-oxoG or a tetrahydrofuran (THF), an abasic site analog (used to represent an oxidized sugar in this study), located in the hairpin loop region were designed to mimic a TNR hairpin with a base lesion in the hairpin loop region. Substrates were constructed by annealing the damaged strands that contained (CAG) 13 or (CAG) 20 repeats to their template strand containing (CTG) 7 repeats at a molar ratio of 1:1.…”
Section: Oligonucleotide Substratesmentioning
confidence: 99%
See 3 more Smart Citations